The Bidirectional Engagement and Equity (BEE) Research Framework to Guide Community-Academic Partnerships: Developed From a Narrative Review and Diverse Stakeholder Perspectives - Jennifer Cunningham‐Erves; Tilicia Mayo‐Gamble; LaNese Campbell; Bishop Calvin Barlow; Claudia Barajas; Jessica L. Jones; Karen Winkfield (Wiley, 2024)
ABSTRACT Background The engagement of community partners in equitable partnerships with academic teams is necessary to achieve health equity. However, there is no standardized approach to support bidirectional engagement among research stakeholders in the context of partnership equity at each phase of the research process. Objective We describe the development of a systematic framework along with competencies and tools promoting bidirectional engagement and equity within community-academic partnerships at each phase of the research process. Design We conducted a four‐step research process between November 2020 and December 2023 for framework development: (1) a narrative literature review; (2) expansion of existing bidirectional, equitable framework; (3) a scientific review with two groups of cognitive interviews (five community engagement researchers and five community leaders and members); and (4) three community‐based organization leader focus groups. Thematic analysis was used to analyse focus group data. Results Using results of each step, the framework was iteratively developed, yielding four phases of the bidirectional engagement and equity (BEE) research framework: Relationship building and assessment of goals and resources (Phase I); form a community-academic partnership based on shared research interests (may include multilevel stakeholders) (Phase II); develop a research team comprising members from each partnering organization (Phase III); and implement the six‐step equitable research process (Phase IV). Bidirectional learning and partnership principles are at the core of the partnership, particularly in Phases II-IV. Competencies and tools for conducting an equitable, engaged research process were provided. Discussion This conceptual framework offers a novel, stepwise approach and competencies for community-academic partners to successfully partner and conduct the research process equitably. Conclusion The BEE research framework can be implemented to standardize the conduct of an equitable, engaged research process within a community-academic partnership, while improving knowledge and trust across partners and, ultimately, an increased return on investment and sustainability to benefit both partners in the area of health outcomes and ultimately health equity. Patient or Public Contribution The development of this framework was co‐led with a community organization in which two leaders in the organization were equitably involved in each phase of the research process, including grant development, study design, participant recruitment, protocol development for focus groups and community and researcher review, framework design and content and dissemination of this manuscript as a co‐author. For grant development, the community leader completed the give‐get grid components for them as a partner. They also wrote up their lived experience in the research process for the progress report. For the focus groups, one community leader co‐led the focus group with the academic partner. For the narrative review, the community leaders did not actively conduct the narrative review but observed the process through the academic partners. One community leader wrote the section 'relationship building' and 'bidirectional learning' sections with the assistance of the academic partner, while they both equally provided input on other sections of the manuscript alongside academic partners. The community leaders have extensive experience in leading programmes, along with partnering with researchers to address health equity issues and improve health outcomes.